Penerapan Manajemen Kredit dalam Upaya Meminimalkan Kredit Bermasalah pada PT. BPR Ambulu Dhanaartha Kabupaten Jember - Indriani, Nisa; Hafidzi, Achmad Hasan; Puspitadewi, Ira; Samsuryaningrum, Samsuryaningrum (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The research was conducted with the aim of knowing the implementation of credit management in minimizing non-performing loans at PT. BPR Ambulu Dhanaatha and find out the various factors that cause problem loans. This research method uses descriptive qualitative methods, data collection techniques using observation, interviews and documentation. From this research, the results obtained (1) PT. BPR Ambulu Dhanaartha implements credit management starting from the planning, organizing, implementing and supervising stages, (2) various factors causing problem loans including a) The account officer made a mistake in analyzing when applying for credit, b) Debtor's business failure, family problems and various other factors which was unexpected. PT. BPR Ambulu Dhanaartha made efforts to minimize problem loans by resheduling, reconditioning, restructuring. Meanwhile, efforts to resolve it are carried out by way of a simple lawsuit to court. Keywords: Credit Management, Factors of non-performing loans, Handling of Non Performing Loans